2018
DOI: 10.1093/humupd/dmy005
|View full text |Cite
|
Sign up to set email alerts
|

The effect of paternal factors on perinatal and paediatric outcomes: a systematic review and meta-analysis

Abstract: Although the increased risks of adverse outcome in offspring associated with paternal factors and identified in this report represent serious health effects, the magnitude of these effects seems modest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
143
2
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(156 citation statements)
references
References 243 publications
(199 reference statements)
5
143
2
6
Order By: Relevance
“…They found that duration of subfertility was one of the prognostic factors for the likelihood of live birth along with abnormal post‐coital test, tubal defect and ovulation defect . As a whole, our present finding that the longer DI, the older the patient, is coupled with everything recently published in meta‐analytical terms regarding the risks of advanced paternal age .…”
Section: Discussionsupporting
confidence: 82%
“…They found that duration of subfertility was one of the prognostic factors for the likelihood of live birth along with abnormal post‐coital test, tubal defect and ovulation defect . As a whole, our present finding that the longer DI, the older the patient, is coupled with everything recently published in meta‐analytical terms regarding the risks of advanced paternal age .…”
Section: Discussionsupporting
confidence: 82%
“…Oldereid et al () published results from a recent systematic review and meta‐analysis investigating paternal age on neonatal and pediatric outcomes. Overall, they concluded that paternal age‐associated increases in offspring serious adverse outcomes were modest.…”
Section: The Aging Male and Offspring Wellnessmentioning
confidence: 99%
“…Animal models of high fat diet-induced paternal obesity and diabetes have found associations with impaired offspring development (11) and offspring metabolic phenotypes and DNA methylation in pancreatic islets (12). In humans, a recent systematic review (13) found conflicting evidence on the association between paternal body mass index (BMI) and offspring birthweight, and some evidence of an association with greater offspring BMI, weight or body fat mass in childhood. A small number of studies have also found links between paternal BMI and sperm or offspring neonatal blood DNA methylation, but these have been based on candidate genes and/or had very limited sample sizes (14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%